Analisis Isi Kuantitatif Kecenderungan Pesan Politik Standup Comedy Alwi Makkasar Di Konten Somasi Pada Chanel Youtube Deddy Corbuzier - Natasya, Resti; Faris, Faris (Prisani Cendekia Institute, 2024)
The purpose of this research is to determine the tendency of political message content in Alwi Makkasar's stand-up comedy material presented in the